1977
DOI: 10.3168/jds.s0022-0302(77)84041-1
|View full text |Cite
|
Sign up to set email alerts
|

Partial Enzymatic Hydrolysis of Whey Protein by Trypsin

Abstract: Partial enzymatic hydrolysis of whey protein by trypsin increased solubility of this protein in water. Water-insoluble, heat-denaturated whey protein was solubilized fully by trypsinization. Optimal conditions for the enzyme reaction, established by the pH-stat technique, were: digestion at pH 8.0 and 55 C for approximately 3 h, at an enzyme-substrate ratio of 1 : 100. Under these conditions, 500 mumoles of titratable protons were liberated per g of substrate in the course of the reaction. Digestion at 40 C ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 8 publications
1
43
0
1
Order By: Relevance
“…Trypsin, e.g., releases several peptides with moderate activity, namely BLG f (22)(23)(24)(25), f(32-40), f(81-83) and (142-148) [35,40,41]. It should be observed that peptides f (22)(23)(24)(25), f (32)(33)(34)(35)(36)(37)(38)(39)(40), and f(81-83) correspond to atypical tryptic cleavages. Several peptides have been isolated from whey protein digested with proteinase K of Tritirachium album; among them is a peptide corresponding to BLG f(78-80) (β-lactosin), which showed the highest ACE-inhibitory activity [1].…”
Section: Ace-inhibitory Activity In Tryptic Hydrolysates Of Blgmentioning
confidence: 99%
See 2 more Smart Citations
“…Trypsin, e.g., releases several peptides with moderate activity, namely BLG f (22)(23)(24)(25), f(32-40), f(81-83) and (142-148) [35,40,41]. It should be observed that peptides f (22)(23)(24)(25), f (32)(33)(34)(35)(36)(37)(38)(39)(40), and f(81-83) correspond to atypical tryptic cleavages. Several peptides have been isolated from whey protein digested with proteinase K of Tritirachium album; among them is a peptide corresponding to BLG f(78-80) (β-lactosin), which showed the highest ACE-inhibitory activity [1].…”
Section: Ace-inhibitory Activity In Tryptic Hydrolysates Of Blgmentioning
confidence: 99%
“…The active peptide inhibitors were purified and identified as α S1 -casein f . Later it was found that the peptides corresponding to β-casein f(177-183), α S1 -casein f (23)(24)(25)(26)(27) and α S1 -casein f (194)(195)(196)(197)(198)(199) had ACE-inhibitory activity [29,30].…”
Section: Ace-inhibitory Activity In Yoghurts Made With Ovine Milkmentioning
confidence: 99%
See 1 more Smart Citation
“…Undenatured whey protein concentrates can be produced by electrodialysis, ion exchange, ultrafiltration and gel filtration (7,104). Oalan (2~ and other workers (4,59,72) suggested that precipitation of denatured whey protein can be achieved by the aid of partial whey proteolysis, polyacrylic acid modification (l24)or succinic anhydride modification (125).…”
Section: Functional Properties Of Wheymentioning
confidence: 99%
“…Whey proteins are relatively resistant to hydrolysis in their native state with the exception to pepsin, trypsin, and chymotrypsin (Jost & Monti, 1977). Trypsin incubation with β-LG for 24 hours resulted in the formation of peptides of less than 2 kDa (Madsen et al, 1997).…”
Section: Trypsinmentioning
confidence: 99%